2020
DOI: 10.1161/str.51.suppl_1.wp478
|View full text |Cite
|
Sign up to set email alerts
|

Abstract WP478: Microglia Knockdown Reduces Inflammation and Improves Post-Stroke Cognitive Impairment in Diabetic Animals

Abstract: Unfortunately, over 40% of stroke victims have pre-existing diabetes which not only increases their risk of stroke up to 2-6 fold, but also worsens both functional recovery and the severity of cognitive impairment. Our lab has recently linked the chronic inflammation that persists in diabetic animals to their poor functional outcomes and exacerbated cognitive impairment, also known as post-stroke cognitive impairment (PSCI). Although we have shown that the development of PSCI in diabetes is associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This approach, inhibition of CSF1R with GW2580, prevents microglial proliferation without affecting their survival (Neal et al, 2020;Olmos-Alonso et al, 2016), and is more translatable to a clinical setting given that complete elimination of microglia is unlikely to be desirable. Increased microglial numbers are also observed in the chronic post-stroke response in white matter and in this condition, depletion of microglia by shRNA targeting of Csf1r has protective effects on white matter integrity and cognitive abilities (Jackson et al, 2020). Collectively, the data suggests sustained microglial proliferation mediates white matter damage and contributes to vascular cognitive impairment.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This approach, inhibition of CSF1R with GW2580, prevents microglial proliferation without affecting their survival (Neal et al, 2020;Olmos-Alonso et al, 2016), and is more translatable to a clinical setting given that complete elimination of microglia is unlikely to be desirable. Increased microglial numbers are also observed in the chronic post-stroke response in white matter and in this condition, depletion of microglia by shRNA targeting of Csf1r has protective effects on white matter integrity and cognitive abilities (Jackson et al, 2020). Collectively, the data suggests sustained microglial proliferation mediates white matter damage and contributes to vascular cognitive impairment.…”
Section: Discussionmentioning
confidence: 81%
“…Inhibition of CSF1R signaling restored white matter integrity to sham levels, providing evidence of a direct contribution of microglia to white matter disruption following chronic cerebral hypoperfusion. Other studies have similarly reported effects of GW2580 treatment to reduce microglial density in chronic disease models (Gerber et al, 2018;Gomez-Nicola et al, 2013;Martinez-Muriana et al, 2016;Neal et al, 2020;Olmos-Alonso et al, 2016) with some studies reporting a protective effect in models with white matter damage (Crespo et al, 2011;Garcia-Agudo et al, 2019;Gerber et al, 2018;Janova et al, 2018;Klein et al, 2015), including that observed in chronic stroke (Jackson et al, 2020). CSF1R/Csf1r is expressed by cells of the myeloid lineage and evidence for functional expression of CSF1R/Csf1r on non-myeloid cells is not compelling (Hume et al, 2020).…”
Section: Discussionmentioning
confidence: 99%